Splenectomy for Aseptic Splenic Abscess - Pranata, Andy Kusuma; Danardono, Edwin Don (Folia Medica Indonesiana, 2021)
Highlight: • A 26-year-old woman have sterile aerobic and anaerobic bacterial cultures. • Pus and splenic tissue examination revealed no bacterial proliferation, while the surgery revealed a splenic abscess. Abstract: We presented a rare case, a 26-year-old woman have sterile aerobic and anaerobic bacterial cultures. Clinical examination of the patient showed a dense cystic mass in the left upper abdomen. Ultrasonography examination suspected a dermoid cyst. However, MRI examination of the abdomen showed turbid cystic lesions. The surgery revealed a splenic abscess, while pus and splenic tissue examination revealed no bacterial proliferation. Based on the literature, the patient had a good prognosis.